Dislocation risk after robotic arm-assisted total hip arthroplasty: a comparison of anterior, lateral and posterolateral approaches. Issue 3 (May 2023) - Marcovigi, Andrea; Sandoni, Dario; Ciampalini, Luigi; Perazzini, Piergiuseppe; Zambianchi, Francesco; Hozack, William J; Catani, Fabio
Aims: Dislocation is a major cause of early failure after THA and is highly influenced by surgical approach and component positioning. Robotic-arm assisted arthroplasty has been developed in an attempt to improve component positioning and reduce postoperative complications. The purpose of this study was to compare the rate of dislocation after robotic total hip arthroplasty through 3 different surgical approaches. Materials and methods: All patients who had undergone robotic arm-assisted THA at 3 centres between 2014 and 2019 were reviewed. After applying exclusion criteria, 1059 patients were included in the study. An anterior approach was used in 323 patients, a lateral approach in 394 and a posterior approach in 342 patients. Episodes of dislocation were recorded after 6 months follow-up. Stem anteversion, cup anteversion, cup inclination and combined anteversion were collected using the integrated navigation system. Cumulative incidence (CI), incidence rate (IR) and risk ratio (RR) were calculated with a confidence interval of 95%. Results: 3 cases of dislocation (2 posterior approach, 1 anterior approach) were recorded, with a dislocation rate of 0.28% and an IR of 0.14%. The rate of placement of the cup in the Lewinnek safe zone was 82.2% for the posterior approach, 82.0% for the lateral approach and 95.4% for the anterior approach. The rate of placement in the combined version safe zone was 98.0% for the posterior approach, 73.0% for the lateral approach and 47.1% for the anterior approach. The incidence rate of dislocation was 0.30% for the anterior approach, 0.34% for the posterior approach and 0% for the lateral approach. Conclusions: The robotic arm-assisted technique is associated with a low risk of dislocation. The combined version technique appears to be a reliable way to reduce the risk of dislocation through the posterolateral approach but does not appear to be essential when using the lateral and anterior approaches.